New hybridization approach of titanium organometallic: PANi thin films as room temperature gas sensors - Izura Izzuddin,; Mohammad Hafizuddin Haji Jumali,; Muhammad Yahaya,; Muhamad Mat Salleh, (Universiti Kebangsaan Malaysia, 2012)
The aim of this research was to investigate the ability of organometallic titanium-PANi hybrid materials as gas sensor at room temperature. To form the hybrid materials, commercially available polyaniline (PANi) powder were directly added into organometallic titanium sols which was synthesized using the sol gel method. The composite films were prepared via spin coating technique followed by electrode deposition for sensors fabrication. Five different organometallic titanium:PANi ratios namely 1 wt% to 5 wt% of PANi were prepared for this experiment. For gas sensing test, all samples were exposed to ethanol vapour. The sensing mode is based on the variation in the electrical conductivity due to the interaction between the gas molecules and the film. It was observed that the composite sensors required appropriate ratio to exhibit optimum sensing properties. This finding proved that the hybridization process is successful and offered much cheaper and easier method for fabrication of room temperature gas sensor